2014
DOI: 10.1186/1472-6920-14-103
|View full text |Cite
|
Sign up to set email alerts
|

Video-based feedback of oral clinical presentations reduces the anxiety of ICU medical students: a multicentre, prospective, randomized study

Abstract: BackgroundOral presentations of clinical cases by medical students during medical rounds in hospital wards are a source of anxiety and little is known about how this anxiety can be alleviated. The objective of this study was to investigate whether video-based feedback of public oral presentations can reduce anxiety in 4th year medical students.MethodsMulticentre randomized study conducted in six intensive care units (ICU) and emergency departments (ED) in France over a 9-month period in 2012. One hundred and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In terms of different forms of feedback, video-feedback has been found to be highly effective, as shown in the acquisition of resuscitation skills [29, 30] and surgical techniques [3133]. In a recently published study on oral presentations of clinical cases publicly presented by medical students, video-assisted, oral feedback reduced severe anxiety during presentations when compared with ‘usual practice’ [34]. However, it remains unclear whether it is feasible to integrate video-feedback into clinical internal medicine routines in the ward setting and if such an innovative model would be accepted.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of different forms of feedback, video-feedback has been found to be highly effective, as shown in the acquisition of resuscitation skills [29, 30] and surgical techniques [3133]. In a recently published study on oral presentations of clinical cases publicly presented by medical students, video-assisted, oral feedback reduced severe anxiety during presentations when compared with ‘usual practice’ [34]. However, it remains unclear whether it is feasible to integrate video-feedback into clinical internal medicine routines in the ward setting and if such an innovative model would be accepted.…”
Section: Introductionmentioning
confidence: 99%
“…In specific relation to VF, it has been previously suggested that anxiety may prevent full student benefit from VF sessions [20]. Whilst one multi-centre randomised study has shown reduced anxiety in relation to oral presentation skills when VF was used, there are no other studies demonstrating similar findings with VF [21]. Indeed, increased perceived anxiety associated with VF in the setting of non-technical skill acquisition has been reported [20,[22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it has been shown that it is possible to gain technical skills in practice with video feedback, such as cardiopulmonary resuscitation or surgical procedures. [7,8] Inadequate control of the anesthesia machine and other anesthesia equipment is a common cause of the possibility of anesthesia errors and associated complications. [9] Therefore, many approaches have been developed for the control before anesthesia applications, and it is aimed to increase patient safety by creating checklists.…”
Section: Introductionmentioning
confidence: 99%